Increasing Public Knowledge about BPJS Kesehatan - Saputra, Raihan Alif; Saputri, Nikmah; Ramadhani, Riszi; Nurcahyaningsih, Intan; Kusumawardhani, Oktavy Budi; Rizky, Wahyu (Urecol Journal. Part C: Health Sciences, 2023)
The Social Security Administering Body (BPJS) for Health is a special institution tasked with administering health insurance for the public, civil servants, and private employees. But until now there are still people who have not registered as BPJS Health participants either independently or paid for by the government. This community service aims to increase the understanding and knowledge of the hamlet community on how to register for BPJS Health and the importance of using BPJS Health. The place for the service to be carried out is in Bakaran Hamlet, RT 01, Sukosari Village, Jumantono, Karanganyar. The method of community service in this activity is through lectures, discussions, and questions and answers about aspects of registration, the latest contributions so as to be able to encourage an increase in public knowledge in general as BPJS users. Before the pre-test was carried out, the result was that 50% of the people did not understand. Then after being given the material, a post test was carried out, there was an increase to 80% of the community understood. In community service activities it can be concluded that the implementation of community service regarding the introduction of BPJS Health can increase public understanding and knowledge.